Can your partner influence your physical activity? The role of social support provided by partners - Rodrigo Wiltgen Ferreira; Marlos Rodrigues Domingues (Revista Brasileira de Atividade Física e Saúde)
The study aims to evaluate the association between social support from partners (SSP) and physica activity (PA) levels. A cross-sectional study conducted in 26 gyms (n = 390) from Pelotas, Rio Grande do Sul, Brazil. Methods: PA was measured using questions about frequency/duration of PA performed at the gym and elsewhere and analyzed as numerical and dichotomized (median). SSP was measured using a validated questionnaire and analyzed in quartiles. Respectively, Linear and Poisson regression were used to assess the associations. SSP was associated with PA in both analyses. Persons belonging to the highest SSP quartile performed 66.1 (95%CI: 11.1 - 121.0) more minutes of PA and had 1.37 (95%CI: 1.01 – 1.85) higher probability to perform more than 300 min/week of PA than those from the lowest SSP quartile. SSP was associated with PA, researchers must consider the potential of SSP when targeting PA behavioral changes.